Maternal risk factors for posterior urethral valves - van der Zanden, Loes F. M.; Groen in ‘t Woud, Sander; van Rooij, Iris A. L. M.; Quaedackers, Josine S. L. T.; Steffens, Martijn; de Wall, Liesbeth L. L.; Schreuder, Michiel F.; Feitz, Wout F. J.; Roeleveld, Nel (Frontiers in Pediatrics, 2023)
INTRODUCTION: Posterior urethral valves (PUV) is a congenital disorder causing an obstruction of the lower urinary tract that affects approximately 1 in 4000 male live births. PUV is considered a multifactorial disorder, meaning that both genetic and environmental factors are involved in its development. We investigated maternal risk factors for PUV. METHODS: We included 407 PUV patients and 814 controls matched on year of birth from the AGORA data- and biobank and three participating hospitals. Information on potential risk factors (family history of congenital anomalies of the kidney and urinary tract (CAKUT), season of conception, gravidity, subfertility and conception using assisted reproductive techniques (ART), plus maternal age, body mass index, diabetes, hypertension, smoking, and use of alcohol and folic acid) was derived from maternal questionnaires. After multiple imputation, adjusted odds ratios (aORs) were estimated using conditional logistic regression corrected for minimally sufficient sets of confounders determined using directed acyclic graphs. RESULTS: A positive family history and low maternal age (<25 years) were associated with PUV development (aORs 3.3 and 1.7 with 95% confidence intervals (95% CI) 1.4-7.7 and 1.0-2.8, respectively), whereas higher maternal age (>35 years) was associated with a lower risk (aOR 0.7 95% CI 0.4-1.0). Maternal preexisting hypertension seemed to increase PUV risk (aOR 2.1 95% CI 0.9-5.1), while gestational hypertension seemed to decrease this risk (aOR 0.6 95% CI 0.3-1.0). Concerning use of ART, the aORs for the different techniques were all above one, but with very wide 95% CIs including one. None of the other factors studied were associated with PUV development. CONCLUSION: Our study showed that family history of CAKUT, low maternal age, and potentially preexisting hypertension were associated with PUV development, whereas higher maternal age and gestational hypertension seemed to be associated with a lower risk. Maternal age and hypertension as well as the possible role of ART in the development of PUV require further research.